The Influence of the Omicron Variant on RNA Extraction and RT-qPCR Detection of SARS-CoV-2 in a Laboratory in Brazil - Lívia Mara Silva; Lorena Rodrigues Riani; Juliana Brovini Leite; Jessica Mara de Assis Chagas; Laura Silva Fernandes; Romário Costa Fochat; Carmen Gomide Pinto Perches; Thiago César Nascimento; Lauren Hubert Jaeger; Marcelo Silva Silvério; Olavo dos Santos Pereira-Júnior; Frederico Pittella (Viruses, 2023)
The emergence of SARS-CoV-2 variants can affect their detection via RT-qPCR. The Omicron variant has a greater affinity for the upper respiratory system and causes clinical conditions similar to bronchitis, as opposed to the pneumonitis-like conditions caused by other SARS-CoV-2 variants. This characteristic increases the viscosity of clinical samples collected for diagnosis. Coinciding with the arrival of the Omicron variant, we observed a failure in control gene expression in our laboratory. In this report, we have optimized a rapid nucleic acid extraction step to restore gene expression and detect the presence of the SARS-CoV-2 virus. We reevaluated 3000 samples, compared variant types occurring in different time periods, and confirmed that the presence of the Omicron variant was responsible for changes observed in the characteristics of these clinical samples. For samples with large amounts of mucus, such as those containing the Omicron variant, a modification to the nucleic acid extraction step was sufficient to restore the quality of RT-qPCR results.